Analasisi dan Perancangan SIG Berbasis Aplikasi Bergerak Sebagai Alternatif Media Promosi UMKM Se-kota Palembang - Sukriyadi Sukriyadi; Iis Pradesan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
Usaha Mikro Kecil dan Menengah (UMKM) have a huge potential in moving economic activities and also become the foundation of a source of income of many people to improve their welfare, along with the great potential that too many things that hinder the development of the UMKM entrepreneurs especially those in the face of market behavior, one inhibiting factor is the manner or media product promotion is done today is still traditional, so the range of opportunities to find new customers become narrow and undeveloped. Based on these needs, the problems encountered in this study is how to do the analysis and design of GIS-based mobile applications in order to facilitate UMKM promotion. This research used RUP as system development methodology that has the object approach in accordance with the programming language used in the construction phase. The data collection process using the method of observation, interviews, and literature. Results from this study is a geographic information system-based mobile applications as an alternative media campaign for UMKM in Palembang.